The importance of post thrombotic syndrome as an outcome after deep venous thrombosis: A survey of Canadian thrombosis clinicians. Issue 159 (November 2017) - Ikesaka, Rick T.; Kahn, Susan R.; Galanaud, Jean-Philippe; Vazquez, Fernando J.; Roche-Nagle, Graham; Carrier, Marc; Le Gal, Gregoire; Rodger, Marc; Gandara, Esteban
Abstract: Objectives: The development of post thrombotic syndrome (PTS) is a major source of morbidity and reduced quality of life. We sought to determine the value assigned by clinicians to post thrombotic syndrome and whether clinicians believe that any post thrombotic syndrome or severe post thrombotic syndrome are important outcomes to assess after deep vein thrombosis (DVT) as compared to other outcomes. Design: The design of the study was a self-responded electronic survey. Questions for the online survey were designed by two authors (R.I. and E.G.). Methods: The survey was distributed to 233 members of Thrombosis Canada and the Canadian Society for Vascular Surgery between August 2014 and October 2014. Results: There were 84 responses to the survey with complete responses were obtained from 71 respondents for a response rate of 36%. PTS was ranked as a significantly less important outcome after DVT than recurrent DVT, pulmonary embolism during treatment, major bleeding, death, quality of life, venous ulceration and severe post thrombotic syndrome (all comparisons p < 0.05 by two sample t-test). Conclusions: Our survey determined that "any post thrombotic syndrome" is perceived by physicians as less important than other DVT outcomes. Thus, "Severe PTS" and not "Any PTS" should be included as an outcome measure in studies investigating acute DVT. Highlights: A online self-response survey study was performed among thrombosis expert physicians. "Any PTS" is not regarded by physicians as an important outcome. "Severe PTS" is deemed important and would be a better outcome in future studies